The Role of Artificial Intelligence Technologies in Public Administration as the Basis for the Development of Municipal Statistics in Ukraine - HINCHUK, L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article discusses the topical issue of integrating artificial intelligence technologies into public administration, with a focus on the development of municipal statistics in Ukraine. It is determined that in the era of digital transformation, AI is identified as one of the key tools for modernizing management processes, allowing for the automation of large-scale data collection and analysis, ensuring effective decision-making, and improving the quality of administrative services. The paper analyzes scientific research and publications that reveal the essence and role of AI in public administration. It is shown that in scientific literature, AI is interpreted as a multifaceted phenomenon that combines philosophical, ethical, and practical aspects, and is also considered a strategic factor in the transformation of political, economic, and social systems. At the same time, the need to take into account the risks associated with unemployment, legal regulation, and ethical challenges is emphasized. The dynamics of investment in AI development in the government sector over the last decade have been studied, which indicates a sharp increase in funding for this area at the global level and the formation of a stable trend towards establishing technologies as a priority area of public administration. Particular attention is paid to the geographical structure of investments and key areas of AI application, among which the provision of administrative services and public safety occupy leading positions. It is emphasized that Ukraine is demonstrating significant progress in the implementation of digital innovations in public administration, as evidenced by the AI readiness index indicators and the successful implementation of projects such as " Diia." A concept for the creation of a chatbot called "Municipal" is proposed, whose task will be to collect, analyze, and forecast municipal statistics, as well as integrate data into a single database. The key functions of the chatbot are outlined and the costs of its implementation are calculated. It is concluded that the introduction of AI into municipal statistics is not only a means of improving the efficiency of local government, but also a necessary condition for Ukraine’s integration into global digital transformation processes.